Miejsce korespondencji w humanistycznym projekcie filozoficznym na przykładzie listów Justusa Lipsjusza do Polaków i Hiszpanów — I - Wojtyniak, Małgorzata (Eslavística Complutense, 2009)
This work analyses the humanist correspondence of Justus Lipsius, the highest representative of Renaissance neostoicism, within the context of his philosophical project. It investigates how the fundamental notions of neostoicim and of sixteenth-century epistolar theory are carried out — according to the humanist ideal — in the correspondence of one of the most relevant representatives of the république des lettres of those times.